Myocardial Resistance to Oxygen and Glucose Deficiency in Severe Brain Injury: Experimental Study - V. V. Rusakov; V. T. Dolgikh (Общая реаниматология)
The purpose of the investigation was to study cardiac contractility in different periods of posttraumatic period and myocardial resistance to oxygen and glucose in severe brain injury (BI).Materials and methods. Experiments were made on 140 male albino rats, by using the isolated isovolumetrically contracted heart procedure, developed by E. T. Fallen et al., 1, 7, and 30 days after injury.Results. Changes in the contractile function of the heart and its metabolism were recorded since day 1 post-BI and they mainly appeared at the stage of reoxygenation after the hypoxic test. The most significant disorders were detected on day 1 after BI in the group of animals with a poor posttraumatic period. Improvement in contractility force and velocity of the isolated hearts following 30 days of injury and in their metabolism was attended by decreased myocar-dial resistance to hypoxia and glucose deficiency.Conclusion. Severe BI is accompanied by depressed cardiac contractility and an increased relationship of the myocardium to the supply with oxygen and glucose, which may be associated with pathogenetic factors, such as hypoxia, impaired bioenergetics, oxidative stress, and Са2+ imbalance.